Las Farianas: Reintegration of former female farc fighters as a driver for peace in Colombia (2019)
The 2016 peace agreement includes comprehensive prescriptions for the so-called 'reincorporation' of former combatants into the social, economic and political life of Colombia. However, the literature is somewhat skeptical regarding the reintegration of female fighters, since they are usually either neglected or are facing intense stigmatization by the society. Nevertheless, based on empirical data from field research in 2018, we argue that both former FARC ex-combatants and conflict-affected communities largely support the reintegration process. This acceptance offers not only prospects for peace but a unique opportunity to promote gender equality in the traditional Colombian society. © 2019, Universidad Nacional de Colombia.